Hazparneko bertsolari xurien eta gorrien arteko azken uztarrak - Xarriton, Piarres (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2009)
In this paper, I present and comment a verse composition of thebertso paper genre, produced in the context of the departmental elections of the Low Pyrenees of 1893 in the locality of Hazparne (Hasparren). I discuss the political situation in which the verses were composed and the significance of the political actors they allude to, as well as the probable authorship of the verses.